Seed yield and fruit quality of habanero pepper with chemical and organic fertilization - Mendoza-Elos, Mariano; Zamudio Alvarez, Luis Felipe; Cervantes Ortiz, Francisco; Chable Moreno, Francisco; Frías Pizano, Jesús; Gámez Vázquez, Alfredo Josué (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of the present investigation consisted in evaluating populations of habanero pepper, with chemical and organic fertilization, for seed and fruit yield. In 2017, at the National Technology of Mexico campus Roque, three genotypes of habanero pepper were established with five different types of fertilization. A group of agronomic variables were evaluated with the SNICS norms. The variables were subjected to an analysis of variance and principal components. The best collection was the Rojo Campeche 12 genotype with an average fruit weight of 4.8 g, 27.5 seeds per fruit and a germination at 16 days of 39.2%. Regarding fertilization, it was determined that the best fruit weight was reached with 50+50% of chemical and organic fertilization. For seeds per fruit and germination, chemical fertilization was better, although statistically similar to the value of combined fertilization (50+50). The above allows to explore genotypes, doses and application opportunities of organic fertilizers that improve seed production and quality, with sustainable and environmentally friendly management.